A modified plastic composite masterbatch and preparation method thereof

By using a combination of functional polycondensate and a variety of performance modification agents, modified plastic composite masterbatches are prepared, which solves the shortcomings of existing plastic masterbatches in terms of mechanical mechanical properties, flame retardancy, heat-resistant aging and antibacterial properties. The preparation of high-performance plastic materials has been realized.

CN118994908BActive Publication Date: 2025-02-14DAQING HANGUANG IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411265223.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-14
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing plastic masterbatches have shortcomings in mechanical and mechanical properties, flame retardancy, heat-resistant aging and antibacterial properties, and it is difficult to meet the market's demand for high-performance plastic materials.

Method used

Functional polycondensation, 3-trimethylmethylmethylamine-2-hydroxypropanesulfonic acid, 1,2,4-trimellitic anhydride chloride, pentafluorobenzoyl chloride, polyphosphoric acid, phosphorus pentaoxide, catalyst, coupling agent , inorganic fillers, polyaminopropyl biguanide, tea polyphenols, antioxidants, environmentally friendly plasticizers and lubricants, and other raw materials are prepared by polycondensation reaction and extrusion granulation process.

Benefits of technology

The mechanical and mechanical properties of the modified plastic composite masterbatch are improved, the flame retardant and heat-resistant aging properties are significantly improved, and the antibacterial properties are also met. The comprehensive performance is stable and suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036929560000081
    Figure BDA0005036929560000081
Patent Text Reader

Abstract

The invention discloses a modified plastic composite masterbatch and a preparation method thereof, and relates to the technical field of polymer materials. The masterbatch comprises the following raw materials in parts by weight: 50-70 parts of a functional polycondensate, 5-7 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1-3 parts of 1,2,4-trimellitic anhydride chloride, 2-4 parts of pentafluorobenzoyl chloride, 0.3-0.5 parts of polyphosphoric acid, 0.5-1 parts of phosphorus pentoxide, 0.5-1 parts of a catalyst, 1-3 parts of a coupling agent, 20-30 parts of an inorganic filler, 1-3 parts of polyaminopropyl biguanide, 1-3 parts of tea polyphenols, 0.5-1 parts of an antioxidant, 3-5 parts of an environmentally friendly plasticizer, and 0.5-1 parts of a lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl. The masterbatch has good mechanical properties, flame retardancy and heat aging resistance, and sufficient antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a modified plastic composite masterbatch and a preparation method thereof. Background Art

[0002] As people's demand for plastic products continues to grow, the requirements for plastic performance and characteristics are also getting higher and higher. As an important raw material in the plastic processing industry, plastic masterbatch plays a vital role in modern industrial manufacturing and has been widely used in food packaging, medical packaging, household appliances, personal care materials, agricultural production materials, auto parts, plastic pipes, engineering plastics, plastic household products and other fields. The formula of plastic masterbatch is very important, and its reasonable composition will directly affect the quality and performance of the final plastic product. It can be seen that it is particularly important to develop plastic masterbatch with good comprehensive performance and performance stability.

[0003] Plastic masterbatch is a concentrate made by attaching an extraordinary amount of plastic additives to resin. When manufacturing plastic products, it is not necessary to add the plastic additives, but only to add the masterbatch with an extraordinary amount in proportion. This has the advantages of simple process, convenient use, easy to realize production automation, improve labor productivity, avoid environmental pollution, and be beneficial to the clean and civilized production of workers. However, the existing plastic masterbatch has more or less technical defects such as single function, limited mechanical properties, flame retardancy and heat aging resistance need to be further improved, and insufficient antibacterial properties.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN110256801B discloses a carbon fiber reinforced ABS plastic masterbatch and its preparation method and use, which contains 90-110 parts by weight of ABS, 10-25 parts by weight of polyether-polyamide block copolymer, and 50-150 parts by weight of carbon fiber with a length of 1-5 mm. The interface compatibility of the resin and the carbon fiber in the carbon fiber reinforced ABS plastic masterbatch of the invention is good, and the carbon fiber is more evenly dispersed; compared with the composite material prepared by directly mixing the carbon fiber with ABS resin, the carbon fiber reinforced ABS composite material prepared by mixing the carbon fiber reinforced ABS plastic masterbatch of the invention with ABS resin has better performance and is more widely used, especially suitable for making automotive materials. However, the flame retardancy, heat aging resistance and antibacterial properties of the masterbatch still need to be further improved.

[0005] It can be seen that the development of a plastic masterbatch with diverse functions, good mechanical properties, excellent flame retardancy and heat aging resistance, and sufficient antibacterial properties meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of polymer materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a modified plastic composite masterbatch having diverse functions, good mechanical properties, good flame retardancy and heat aging resistance, and sufficient antibacterial properties, and a preparation method thereof.

[0007] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: a modified plastic composite masterbatch, comprising the following raw materials in parts by weight: 50-70 parts of functional polycondensate, 5-7 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1-3 parts of 1,2,4-trimellitic anhydride chloride, 2-4 parts of pentafluorobenzoyl chloride, 0.3-0.5 parts of polyphosphoric acid, 0.5-1 parts of phosphorus pentoxide, 0.5-1 parts of catalyst, 1-3 parts of coupling agent, 20-30 parts of inorganic filler, 1-3 parts of polyaminopropyl biguanide, 1-3 parts of tea polyphenols, 0.5-1 parts of antioxidant, 3-5 parts of environmentally friendly plasticizer, and 0.5-1 parts of lubricant; the functional polycondensate is made by condensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0008] Preferably, the preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are mixed evenly, and then added to a reaction kettle connected to a water separator, and the air in the kettle is replaced with nitrogen. Under nitrogen protection, the mixture is stirred and reacted at 130-140°C for 2-4 hours, and the water and toluene generated during the reaction are removed through the water separator. The mixture is then heated to 160-170°C, and the stirring reaction is continued for 12-16 hours. The mixture is then cooled to room temperature and precipitated in water. The precipitated polymer is washed with ethanol for 3-6 times, and finally dried in a vacuum drying oven at 90-95°C to constant weight to obtain a functional polycondensate.

[0009] Preferably, the molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:(1-2):(10-20):5.

[0010] Preferably, the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of (1-2):1.

[0011] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0012] Preferably, the inorganic filler is a mixture of boron fiber, graphene oxide, and nano zinc oxide in a mass ratio of (2-4):1:(0.8-1.2).

[0013] Preferably, the boron fiber has an average diameter of 3-9 μm and a length of 1-5 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 0.5-5 μm and a thickness of 0.8-1.2 nm; and the nano zinc oxide has a particle size of 10-80 nm.

[0014] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168.

[0015] Preferably, the environmentally friendly plasticizer is epoxidized soybean oil.

[0016] Preferably, the lubricant is at least one of pentaerythritol stearate and ethylene bisstearamide.

[0017] Another object of the present invention is to provide a method for preparing the modified plastic composite masterbatch, comprising the following steps: mixing the raw materials evenly to obtain a mixed material, adding the mixed material to a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch.

[0018] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0019] (1) The preparation method of the modified plastic composite masterbatch disclosed in the present invention only requires the raw materials to be uniformly mixed and then extruded into granules, without the need for special equipment, low capital investment, low energy consumption and labor intensity, small impact on the environment, high preparation efficiency and finished product qualification rate, suitable for continuous large-scale production, and has high promotion and application value.

[0020] (2) The modified plastic composite masterbatch disclosed in the present invention comprises the following raw materials in parts by weight: 50-70 parts of functional polycondensate, 5-7 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1-3 parts of 1,2,4-trimellitic anhydride chloride, 2-4 parts of pentafluorobenzoyl chloride, 0.3-0.5 parts of polyphosphoric acid, 0.5-1 parts of phosphorus pentoxide, 0.5-1 parts of catalyst, 1-3 parts of coupling agent, 20-30 parts of inorganic filler, 1-3 parts of polyaminopropyl biguanide, 1-3 parts of tea polyphenols, 0.5-1 parts of antioxidant, 3-5 parts of environmentally friendly plasticizer, and 0.5-1 parts of lubricant; the functional polycondensate is prepared by condensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl. Through the mutual cooperation between the raw materials, the modified plastic composite masterbatch can simultaneously achieve the functional advantages of good mechanical properties, flame retardancy and heat aging resistance, and sufficient antibacterial properties. The introduction of polar groups such as hydroxymethyl and anhydride through 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid and 1,2,4-trimellitic anhydride chloride is beneficial to improve the compatibility between the functional condensation polymer and other raw materials, and improve the performance stability and comprehensive performance of plastic products when the masterbatch is used.

[0021] (3) The modified plastic composite masterbatch disclosed in the present invention, the functional polycondensate is made by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl. Fluorenone, phenylsulfone, phenyl ether and biphenyl structures are introduced into the polymer molecular structure at the same time, and the trimellitic anhydride and pentafluorobenzene structures introduced by other raw materials give the product excellent mechanical properties, heat aging resistance and flame retardant properties under the multiple effects of electronic effect, steric effect and conjugation effect; the combination of polyaminopropyl biguanide, tea polyphenols, graphene oxide and nano zinc oxide can also improve the antibacterial properties of the product.

[0022] (4) The modified plastic composite masterbatch disclosed in the present invention, wherein the inorganic filler is a mixture of boron fiber, graphene oxide, and nano zinc oxide in a mass ratio of (2-4):1:(0.8-1.2). By rationally selecting the composition, after the inorganic filler is added to the raw materials for preparing the masterbatch, it cooperates with other raw materials, not only having good compatibility, but also improving mechanical properties and antibacterial properties at the same time. DETAILED DESCRIPTION

[0023] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0024] Example 1

[0025] A modified plastic composite masterbatch comprises the following raw materials in parts by weight: 50 parts of functional polycondensate, 5 parts of 3-trihydroxymethylmethylamine-2-hydroxypropanesulfonic acid, 1 part of 1,2,4-trimellitic anhydride chloride, 2 parts of pentafluorobenzoyl chloride, 0.3 parts of polyphosphoric acid, 0.5 parts of phosphorus pentoxide, 0.5 parts of catalyst, 1 part of coupling agent, 20 parts of inorganic filler, 1 part of polyaminopropyl biguanide, 1 part of tea polyphenols, 0.5 parts of antioxidant, 3 parts of environmentally friendly plasticizer, and 0.5 parts of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0026] The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, and the air in the kettle is replaced with nitrogen, and the reaction is stirred at 130°C for 2h under nitrogen protection, and the water and toluene generated in the reaction process are removed through the water separator, and then the temperature is raised to 160°C, and the stirring reaction is continued for 12h. , then cooled to room temperature, precipitated in water, washed the precipitated polymer with ethanol three times, and finally dried in a vacuum drying oven at 90°C to constant weight to obtain a functional polycondensate; the molar ratio of 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide, and toluene is 1:1:1:10:5; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1:1. The M of the obtained functional polycondensate was measured by GPC test. n =14829 g / mol, M W / M n =1.359; through elemental analysis and weight change calculation, the molar ratio of the structural units introduced by 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl in the functional polycondensate is about 1:1, which is the same as the theoretical value.

[0027] The coupling agent is silane coupling agent KH550; the inorganic filler is a mixture of boron fiber, graphene oxide and nano zinc oxide in a mass ratio of 2:1:0.8; the average diameter of the boron fiber is 3 μm and the length is 1 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 0.5 μm and a thickness of 0.8 nm; the particle size of the nano zinc oxide is 10 nm; the antioxidant is antioxidant 1010; the environmentally friendly plasticizer is epoxidized soybean oil; and the lubricant is pentaerythritol stearate.

[0028] A method for preparing the modified plastic composite masterbatch comprises the following steps: uniformly mixing the raw materials to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch; the extrusion temperature of the twin-screw extruder is 240°C, and the screw speed is 190rpm.

[0029] Example 2

[0030] A modified plastic composite masterbatch comprises the following raw materials in parts by weight: 55 parts of functional polycondensate, 5.5 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1.5 parts of 1,2,4-trimellitic anhydride chloride, 2.5 parts of pentafluorobenzoyl chloride, 0.35 parts of polyphosphoric acid, 0.6 parts of phosphorus pentoxide, 0.6 parts of catalyst, 1.5 parts of coupling agent, 23 parts of inorganic filler, 1.5 parts of polyaminopropyl biguanide, 1.5 parts of tea polyphenols, 0.6 parts of antioxidant, 3.5 parts of environmentally friendly plasticizer and 0.6 parts of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0031] The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, and the air in the kettle is replaced with nitrogen. Under the protection of nitrogen, the mixture is stirred and reacted at 133°C for 2.5 hours, and water and toluene generated during the reaction are removed through the water separator. The mixture is then heated to 163°C, and the mixture is stirred and reacted for 13 hours. The mixture is then cooled to room temperature and precipitated in water. The precipitated polymer is washed with ethanol for 4 times, and finally dried in a vacuum drying oven at 91°C to a constant weight to obtain the functional polycondensate. The molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:1.2:13:5.

[0032] The catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.3:1; the coupling agent is a silane coupling agent KH560; the inorganic filler is a mixture of boron fiber, graphene oxide, and nano zinc oxide in a mass ratio of 2.5:1:0.9; the average diameter of the boron fiber is 4 μm and the length is 2 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 2 μm and a thickness of 0.9 nm; the particle size of the nano zinc oxide is 20 nm; the antioxidant is antioxidant 1076; the environmentally friendly plasticizer is epoxy soybean oil; and the lubricant is ethylene bisstearamide.

[0033] A method for preparing the modified plastic composite masterbatch comprises the following steps: uniformly mixing the raw materials to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch; the extrusion temperature of the twin-screw extruder is 240°C, and the screw speed is 200rpm.

[0034] Example 3

[0035] A modified plastic composite masterbatch comprises the following raw materials in parts by weight: 60 parts of functional polycondensate, 6 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 2 parts of 1,2,4-trimellitic anhydride chloride, 3 parts of pentafluorobenzoyl chloride, 0.4 parts of polyphosphoric acid, 0.75 parts of phosphorus pentoxide, 0.75 parts of catalyst, 2 parts of coupling agent, 25 parts of inorganic filler, 2 parts of polyaminopropyl biguanide, 2 parts of tea polyphenols, 0.8 parts of antioxidant, 4 parts of environmentally friendly plasticizer, and 0.7 parts of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0036] The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, and the air in the kettle is replaced with nitrogen. Under the protection of nitrogen, the mixture is stirred and reacted at 135°C for 3 hours, and water and toluene generated during the reaction are removed through the water separator. The mixture is then heated to 165°C, and the mixture is stirred and reacted for 14 hours. The mixture is then cooled to room temperature and precipitated in water. The precipitated polymer is washed with ethanol for 5 times, and finally dried in a vacuum drying oven at 93°C to a constant weight to obtain the functional polycondensate. The molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:1.5:15:5.

[0037] The catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.5:1; the coupling agent is a silane coupling agent KH570; the inorganic filler is a mixture of boron fiber, graphene oxide, and nano zinc oxide in a mass ratio of 3:1:1; the average diameter of the boron fiber is 6 μm and the length is 3.5 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 3 μm and a thickness of 1 nm; the particle size of the nano zinc oxide is 50 nm; the antioxidant is antioxidant 168; the environmentally friendly plasticizer is epoxidized soybean oil; and the lubricant is pentaerythritol stearate.

[0038] A method for preparing the modified plastic composite masterbatch comprises the following steps: uniformly mixing the raw materials to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch; the extrusion temperature of the twin-screw extruder is 240°C, and the screw speed is 210rpm.

[0039] Example 4

[0040] A modified plastic composite masterbatch comprises the following raw materials in parts by weight: 65 parts of functional polycondensate, 6.5 parts of 3-trihydroxymethylmethylamine-2-hydroxypropanesulfonic acid, 2.5 parts of 1,2,4-trimellitic anhydride chloride, 3.5 parts of pentafluorobenzoyl chloride, 0.45 parts of polyphosphoric acid, 0.9 parts of phosphorus pentoxide, 0.9 parts of catalyst, 2.5 parts of coupling agent, 29 parts of inorganic filler, 2.5 parts of polyaminopropyl biguanide, 2.5 parts of tea polyphenols, 0.9 parts of antioxidant, 4.5 parts of environmentally friendly plasticizer and 0.9 parts of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0041] The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, and the air in the kettle is replaced with nitrogen. Under the protection of nitrogen, the mixture is stirred and reacted at 138°C for 3.5 hours, and water and toluene generated during the reaction are removed through the water separator. The mixture is then heated to 168°C, and the mixture is stirred and reacted for 15 hours. The mixture is then cooled to room temperature and precipitated in water. The precipitated polymer is washed with ethanol for 5 times, and finally dried in a vacuum drying oven at 94°C to a constant weight to obtain the functional polycondensate. The molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:1.8:18:5.

[0042] The catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.8:1; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570 in a mass ratio of 1:3:2; the inorganic filler is a mixture of boron fiber, graphene oxide and nano zinc oxide in a mass ratio of 3.5:1:1.1; the average diameter of the boron fiber is 8 μm and the length is 4 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 4.5 μm and a thickness of 1.1 nm; the particle size of the nano zinc oxide is 70 nm; the antioxidant is a mixture of antioxidant 1010, antioxidant 1076 and antioxidant 168 in a mass ratio of 1:2:3; the environmentally friendly plasticizer is epoxy soybean oil; and the lubricant is a mixture of pentaerythritol stearate and ethylene bisstearamide in a mass ratio of 3:5.

[0043] A method for preparing the modified plastic composite masterbatch comprises the following steps: uniformly mixing the raw materials to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch; the extrusion temperature of the twin-screw extruder is 240°C, and the screw speed is 210rpm.

[0044] Example 5

[0045] A modified plastic composite masterbatch comprises the following raw materials in parts by weight: 70 parts of functional polycondensate, 7 parts of 3-trihydroxymethylmethylamine-2-hydroxypropanesulfonic acid, 3 parts of 1,2,4-trimellitic anhydride chloride, 4 parts of pentafluorobenzoyl chloride, 0.5 parts of polyphosphoric acid, 1 part of phosphorus pentoxide, 1 part of catalyst, 3 parts of coupling agent, 30 parts of inorganic filler, 3 parts of polyaminopropyl biguanide, 3 parts of tea polyphenols, 1 part of antioxidant, 5 parts of environmentally friendly plasticizer and 1 part of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl.

[0046] The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, and the air in the kettle is replaced with nitrogen. Under the protection of nitrogen, the mixture is stirred and reacted at 140°C for 4 hours, and water and toluene generated during the reaction are removed through the water separator. The mixture is then heated to 170°C, and the mixture is stirred and reacted for 16 hours. The mixture is then cooled to room temperature and precipitated in water. The precipitated polymer is washed with ethanol for 6 times, and finally dried in a vacuum drying oven at 95°C to a constant weight to obtain the functional polycondensate. The molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:2:20:5.

[0047] The catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 2:1; the coupling agent is a silane coupling agent KH550; the inorganic filler is a mixture of boron fiber, graphene oxide, and nano zinc oxide in a mass ratio of 4:1:1.2; the average diameter of the boron fiber is 9 μm and the length is 5 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 5 μm and a thickness of 1.2 nm; the particle size of the nano zinc oxide is 80 nm; the antioxidant is antioxidant 1010; the environmentally friendly plasticizer is epoxy soybean oil; and the lubricant is ethylene bisstearamide.

[0048] A method for preparing the modified plastic composite masterbatch comprises the following steps: uniformly mixing the raw materials to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch; the extrusion temperature of the twin-screw extruder is 240°C, and the screw speed is 195rpm.

[0049] Comparative Example 1

[0050] A modified plastic composite masterbatch and a preparation method thereof are substantially the same as those of Example 1, except that pentafluorobenzoyl chloride and 3-trihydroxymethylmethylamine-2-hydroxypropanesulfonic acid are not added.

[0051] Comparative Example 2

[0052] A modified plastic composite masterbatch and a preparation method thereof are substantially the same as those of Example 1, except that 1,2,4-trimellitic anhydride chloride is not added and graphene oxide is used instead of nano zinc oxide.

[0053] In order to further illustrate the beneficial technical effects of the modified plastic composite masterbatch and the preparation method thereof involved in each embodiment of the present invention, relevant performance tests were performed on the modified plastic composite masterbatch and the preparation method thereof involved in Examples 1-5 and Comparative Examples 1-2; the test method is as follows:

[0054] (1) Tensile properties: Tensile strength test is carried out according to GB / T 1040.1-2018.

[0055] (2) Heat aging resistance: Each modified plastic composite masterbatch product was placed in hot air at 85°C for artificial accelerated aging for 168 hours. After cooling to room temperature, the tensile strength was measured again. The heat aging resistance was measured by the retention rate of tensile strength. The larger the value, the better the heat aging resistance.

[0056] (3) Flame retardancy: The limiting oxygen index test was carried out according to the method in GBT2406.2-2009 Oxygen index method for plastics to determine the combustion behavior Part 2: Room temperature test.

[0057] (4) Antibacterial property: The antibacterial property of the product was tested by referring to the method of GB / T31402-2015, and the product was placed at room temperature for 3 months after preparation. The test bacteria were Escherichia coli and Staphylococcus aureus.

[0058] Table 1

[0059]

[0060] As can be seen from Table 1, the modified plastic composite masterbatch involved in each embodiment of the present invention has better mechanical properties, more excellent heat aging resistance, flame retardancy and antibacterial properties than the comparative example products, and the combined use of pentafluorobenzoyl chloride, 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1,2,4-trimellitic anhydride chloride, graphene oxide and nano zinc oxide is beneficial to improving the above properties.

[0061] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified plastic composite masterbatch, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of functional polycondensate, 5-7 parts of 3-trimethylolmethylamine-2-hydroxypropanesulfonic acid, 1-3 parts of 1,2,4-trimellitic anhydride chloride, 2-4 parts of pentafluorobenzoyl chloride, 0.3-0.5 parts of polyphosphoric acid, 0.5-1 parts of phosphorus pentoxide, 0.5-1 parts of catalyst, 1-3 parts of coupling agent, 20-30 parts of inorganic filler, 1-3 parts of polyaminopropyl biguanide, 1-3 parts of tea polyphenols, 0.5-1 parts of antioxidant, 3-5 parts of environmentally friendly plasticizer, and 0.5-1 parts of lubricant; the functional polycondensate is prepared by polycondensation reaction of 2,7-dihydroxy-9-fluorenone and 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl; the catalyst is a mixture formed by mixing anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of (1-2):1; The preparation method of the modified plastic composite masterbatch comprises the following steps: mixing various raw materials uniformly to obtain a mixed material, adding the mixed material into a twin-screw extruder, and extruding and granulating to obtain the modified plastic composite masterbatch.

2. The modified plastic composite masterbatch according to claim 1, characterized in that: The preparation method of the functional polycondensate comprises the following steps: 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene are uniformly mixed, and then added into a reaction kettle connected with a water separator, the air in the kettle is replaced with nitrogen, and under nitrogen protection, the reaction is stirred at 130-140°C for 2-4h, water and toluene generated during the reaction are removed through the water separator, and then the temperature is raised to 160-170°C, the reaction is continued with stirring for 12-16h, and then the temperature is cooled to room temperature, and the polymer is precipitated in water, and the precipitated polymer is washed with ethanol for 3-6 times, and finally the polymer is placed in a vacuum drying oven at 90-95°C and dried to constant weight to obtain the functional polycondensate.

3. The modified plastic composite masterbatch according to claim 2, characterized in that: The molar ratio of the 2,7-dihydroxy-9-fluorenone, 4,4'-bis(4-chlorophenylsulfone)-1,1'-biphenyl, cesium carbonate, dimethyl sulfoxide and toluene is 1:1:(1-2):(10-20):

5.

4. The modified plastic composite masterbatch according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

5. The modified plastic composite masterbatch according to claim 1, characterized in that: The inorganic filler is a mixture of boron fiber, graphene oxide and nano zinc oxide in a mass ratio of (2-4):1:(0.8-1.2).

6. The modified plastic composite masterbatch according to claim 5, characterized in that: The average diameter of the boron fiber is 3-9 μm and the length is 1-5 mm; the graphene oxide is a single-layer graphene oxide with a particle size of 0.5-5 μm and a thickness of 0.8-1.2 nm; and the particle size of the nano zinc oxide is 10-80 nm.

7. The modified plastic composite masterbatch according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 1076 , and antioxidant 168 .

8. The modified plastic composite masterbatch according to claim 1, characterized in that: The environmentally friendly plasticizer is epoxidized soybean oil; the lubricant is at least one of pentaerythritol stearate and ethylene bisstearamide.

Citation Information

Patent Citations

  • A carbon fiber reinforced ABS plastic masterbatch, its preparation method and uses

    CN110256801B

  • Fluorenyl poly(ether-ether-ketone-ketone-ketone) thermoplastic resin and preparation method thereof

    CN104292452A

  • Polycarbonate compositions having improved thermal dimensional stability and high refractive index

    CN104918981A